Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Functional plasticity of HCO3– uptake and CO2 fixation in Cupriavidus necator H16 - Justin Panich; Emili Toppari; Sara Tejedor-Sanz; Bonnie Fong; Eli Dugan; Yan Chen; Christopher J. Petzold; Zhiying Zhao; Yasuo Yoshikuni; David F. Savage; Steven W. Singer (Bioresource Technology, 2024)

Revealing oxidative pentose metabolism in new Pseudomonas putida isolates - Mee‐Rye Park; Rahul Gauttam; Bonnie Fong; Yan Chen; Hyun Gyu Lim; Adam M. Feist; Aindrila Mukhopadhyay; Christopher J. Petzold; Blake A. Simmons; Steven W. Singer (Environmental Microbiology, 2023)
The Pseudomonas putida group in the Gammaproteobacteria has been intensively studied for bioremediation and plant growth promotion. Members of this group have recently emerged as promising hosts to convert intermediates derived from plant biomass to biofuels and biochemicals. However, most strains of P. putida cannot metabolize pentose sugars derived from hemicellulose. Here, we describe three isolates that provide a broader view of the pentose sugar catabolism in the P. putida group. One of these isolates clusters with the well‐characterized P. alloputida KT2440 (Strain BP6); the second isolate clustered with plant growth‐promoting strain P. putida W619 (Strain M2), while the third isolate represents a new species in the group (Strain BP8). Each of these isolates possessed homologous genes for oxidative xylose catabolism ( xylDXA ) and a potential xylonate transporter. Strain M2 grew on arabinose and had genes for oxidative arabinose catabolism ( araDXA ). A CRISPR interference (CRISPRi) system was developed for strain M2 and identified conditionally essential genes for xylose growth. A glucose dehydrogenase was found to be responsible for initial oxidation of xylose and arabinose in strain M2. These isolates have illuminated inherent diversity in pentose catabolism in the P. putida group and may provide alternative hosts for biomass conversion.

Purification and characterization of a native lytic polysaccharide monooxygenase from Thermoascus aurantiacus - Susanne Fritsche; Cynthia Hopson; Jennifer Gorman; Raphael Gabriel; Steven W. Singer (Biotechnology Letters, 2020)

Genomic Analysis of Xylose Metabolism in Members of the Deinoccocus-Thermus Phylum from Thermophilic Biomass-Deconstructing Bacterial Consortia - Yu-Wei Wu; Chijioke Joshua; Stephanie A. Eichorst; John M. Gladden; Blake A. Simmons; Steven W. Singer (BioEnergy Research, 2015)

Community dynamics of cellulose‐adapted thermophilic bacterial consortia - Stephanie A. Eichorst; Patanjali Varanasi; Vatalie Stavila; Marcin Zemla; Manfred Auer; Seema Singh; Blake A. Simmons; Steven W. Singer (Environmental Microbiology, 2013)
Summary Enzymatic hydrolysis of cellulose is a key process in the global carbon cycle and the industrial conversion of biomass to biofuels. In natural environments, cellulose hydrolysis is predominately performed by microbial communities. However, detailed understanding of bacterial cellulose hydrolysis is primarily confined to a few model isolates. Developing models for cellulose hydrolysis by mixed microbial consortia will complement these isolate studies and may reveal new mechanisms for cellulose deconstruction. Microbial communities were adapted to microcrystalline cellulose under aerobic, thermophilic conditions using green waste compost as the inoculum to study cellulose hydrolysis in a microbial consortium. This adaptation selected for three dominant taxa – the F irmicutes, B acteroidetes and T hermus . A high‐resolution profile of community development during the enrichment demonstrated a community transition from F irmicutes to a novel B acteroidetes population that clusters in the C hitinophagaceae family. A representative strain of this population, strain NYFB , was successfully isolated, and sequencing of a nearly full‐length 16S rRNA gene demonstrated that it was only 86% identical compared with other validated strains in the phylum B acteroidetes . Strain NYFB grew well on soluble polysaccharide substrates, but grew poorly on insoluble polysaccharide substrates. Similar communities were observed in companion thermophilic enrichments on insoluble wheat arabinoxylan, a hemicellulosic substrate, suggesting a common model for deconstruction of plant polysaccharides. Combining observations of community dynamics and the physiology of strain NYFB , a cooperative successional model for polysaccharide hydrolysis by the F irmicutes and B acteroidetes in the thermophilic cellulolytic consortia is proposed.

Strategies for Enhancing the Effectiveness of Metagenomic-based Enzyme Discovery in Lignocellulolytic Microbial Communities - Kristen M. DeAngelis; John M. Gladden; Martin Allgaier; Patrik D’haeseleer; Julian L. Fortney; Amitha Reddy; Philip Hugenholtz; Steven W. Singer; Jean S. Vander Gheynst; Whendee L. Silver; Blake A. Simmons; Terry C. Hazen (BioEnergy Research, 2010)

New insights into the mechanism of nickel insertion into carbon monoxide dehydrogenase: analysis of Rhodospirillum rubrum carbon monoxide dehydrogenase variants with substituted ligands to the [Fe3S4] portion of the active-site C-cluster - Won Bae Jeon; Steven W. Singer; Paul W. Ludden; Luis M. Rubio (JBIC Journal of Biological Inorganic Chemistry, 2005)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)